The Influence of Teacher staffing levels on quality of education in public day secondary schools in Embu County, Kenya (International Journal of Scientific Research and Management (IJSRM), 2022)
Abstract Amongst all educational personnel it is teachers who arguably play the central role of giving purpose to the learners and enthuse in them the drive to work hard so as to succeed in in life. By virtue of this vital function, number of teachers and their qualifications are key determinants of student’s test scores, completion rates, enrollment rates, repetition and dropout rates as indicators of quality of education. The study envisioned to examine the influence of teacher staffing levels on quality of education in public day secondary schools in Embu County, Kenya. The study used correlational research design and targeted 192 principals, 1743 teachers and 35124 students from all the 192 public secondary schools in Embu County. Schools were stratified into the five Sub-Counties of Embu County. Public day secondary schools were purposefully sampled followed by another purposeful sampling of form four students. The study used a sample of 516 individuals comprising of 35 school principals, 97 teachers and 384 students. Data was collected using questionnaires, interview schedule and an observation checklist. The SPSS software was used to aid in data analysis. The study revealed that teacher staffing levels had strong correlation with quality of education. Chi-square statistics computed at α=0.05 established a significant relationship between number of teachers and quality of education. The findings of the study revealed that public day secondary schools were understaffed pursuant to the curriculum based establishment. The study recommended that the government through the teacher service commission should employ more teachers to alleviate the shortage of teachers